LEVELING OF CRITICAL THINKING ABILITIES OF STUDENTS OF MATHEMATICS EDUCATION IN MATHEMATICAL PROBLEM SOLVING - Rasiman, Rasiman (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2015)
This research aims to determine the leveling of critical thinking abilities of students of mathematics education in mathematical problem solving. It includes qualitative-explorative study that conducted at University of PGRI Semarang. The generated data in the form of information obtained problem solving question and interview guides. The results are: (1) students who are not critical (LCTA-0) only able to identify the given facts clearly, (2) students are less critical (LCTA-1), students can identify the facts in problems, (3) critical student (LCTA-2), students can identify the fact in problems, revealing the prerequisite knowledge appropriately, solve the problem but still less accurate in every stage, and (4) students are very critical (LCTA-3), students can identify the facts given clearly, mention the concept/ theorem/ prerequisite material. Based on these results, the leveling of students critical thinking abilities can be applied in a lecture at mathematics education.Keywords: leveling, critical thinking, mathematical problemÃ‚Â DOI: dx.doi.org/10.22342/jme.61.40